Recurrent Vulvovaginal Candidiasis: Assessing the relationship between feminine/vaginal washes and other factors among Ghanaian women - Emmanuel Otoo-Annan; Vivian Efua Senoo-Dogbey (BMC, 2024)
Abstract Introduction Vulvovaginal Candidiasis (VVC) is a public health problem, with approximately 30-50% of women affected at least once during their lifetime. Recurrent Vulvovaginal Candidiasis (RVVC) is diagnosed following three or four repeated episodes of VVC in a calendar year. This condition poses health concerns with significant impacts on the quality of life of women. This cross-sectional study estimated the prevalence of RVVC and assessed the relationship between feminine/vaginal washes and other factors on RVVC among Ghanaian women in the Sekondi/Takoradi Metropolis. Methodology A cross-sectional study was employed to gather data from 304 women. Data were collected using a pretested questionnaire. Bivariate and multivariate analyses, including chi-square/Fisher's exact test and logistic regression, were performed using Jamovi (R Core Team 2021) software. Proportions were calculated, and odds ratios and their corresponding 95% confidence intervals were computed with the level of significance set at 0.05. Results The prevalence of RVVC was estimated as 48.4% (95% CI 42.6%, 54.1%). Feminine Vaginal wash use (aOR = 3.86; 95% CI = 2.18, 6.84); age 36-45 years (aOR = 0.36; 95% CI = 0.17, 0.76) marital status (aOR = 2.37; 95% CI = 1.17, 4.79) and Sexual activity (aOR:0.43: 95%CI = 0.21, 0.88) were significantly associated with RVVC with p < 0.005. Conclusion RVVC is prevalent among women in the Sekondi/Takoradi Metropolis of Ghana. Feminine/Vaginal washes could be cautiously linked to the development of RVVC.